Nasal biometrics and nasofacial proportion in Hausas and Yorubas using Akinlolu-Raji image-processing algorithm - Adelaja, AkinloluAbdulazeez (CHRISMED Journal of Health and Research, 2016)
Background: Nasal biometrics is vital to facial analyses. This study evaluated nasal biometrics in Hausas and Yorubas of Nigeria. Materials and Methods: Hausas (150 males and 150 females, aged 18-36 years) and Yorubas (150 males and 150 females, aged 15-33 years) were selected as subjects with informed consents and when established as Hausas or Yorubas by parents and grandparents. Height, body weight and cephalometric parameters (evaluated on three-dimensional facial photographs) were measured on subjects. The novel Akinlolu-Raji image-processing algorithm was developed using modified row method of computer programming. Nasal root width, nose height, nose width, nasal bridge length, nasal tip protrusion, nasal index, facial width and nasofacial proportion computed from readings of Akinlolu-Raji image-processing algorithm were analyzed using Z-test (P ≤ 0.05) of 2010 Microsoft Excel statistical software. Results: Computed nasal biometrics showed statistically nonsignificant higher values (P > 0.05) in males of Hausas (100%) and Yorubas (80%) compared to their female counterparts. In addition, results showed nonsignificant higher values (P > 0.05) in 80% of nasal biometrics in Hausas compared to Yorubas in both sexes. Based on classifications of nose types from nasal index, Hausas have the platyrrhine nose type while Yorubas have the mesorrhine nose type. Nasofacial proportion was lower in Hausa males compared to females, but of same values in Yoruba males and females. In addition, nasofacial proportions were lower in Hausas compared to Yorubas in both sexes. Conclusions: Sexual dimorphism of nasal biometrics exists between sexes of Hausas and Yorubas. Furthermore, Hausas and Yorubas are of similar nasal sizes.